Non-Verbal Communication and Its Role in Teacher-Student Interaction: A Literature Review - Nurhayati, Nurhayati; Dollah, Syarifuddin (Pascasarjana Universitas Negeri Makassar, 2025)
This study aims to explore the role of non-verbal communication in teacher-student interactions, focusing on its impact on learning, engagement, and classroom dynamics. Non-verbal communication, encompassing gestures, facial expressions, body language, and eye contact, is often an unspoken but powerful aspect of interpersonal communication in educational settings. The research methodology involved a literature review of existing studies and scholarly articles published over the last two decades, providing insights into how non-verbal cues influence the classroom environment. The findings highlight that non-verbal communication plays a crucial role in fostering effective teacher-student relationships, enhancing student engagement, and conveying emotions, intentions, and feedback that may not be expressed verbally. Key aspects such as teachers' use of positive body language, facial expressions, and non-verbal cues were found to significantly impact student motivation, comfort, and learning outcomes. Furthermore, the review identifies cultural differences in the interpretation of non-verbal signals and emphasizes the importance of teachers' awareness of these factors. Based on the findings, it is recommended that teacher training programs incorporate training on non-verbal communication skills to improve classroom interaction. Additionally, future research should explore the interaction between verbal and non-verbal cues in different educational contexts and across diverse cultural settings. In conclusion, non-verbal communication is an integral component of effective teacher-student interaction, shaping the educational experience in subtle but profound ways. Teachers who are attuned to non-verbal signals can create a more supportive and engaging learning environment, ultimately enhancing student learning outcomes.